(untitled) (Nóema, 2015)
The problem of the subject’s matter is a difficult and controversial topic, already tackled at the origin of Western thought: Plato and Aristotle drew its essential boundaries. Democritus, Epicurus and the Stoics marked a kind of countermelody of this theme. Together with modern science on the one hand and Hegelian-Marxist historicism on the other, new horizons and new boundaries, new ways to consider and theorize the notions of subject and matter were added to the issue. Today, a new reset of the whole problem concerning the matter of subjectivityseems to be necessary: this new approach cannot ignore the concrete practice of pre-categorial discourses and the materiality of the supports and of the socio-economic and technological connections through which these discourses occur and are made possible. Hence, a new «materialistic» posture seems to delineate together with a new view of subjectivity.